"Raising HOPE": Improved Outcomes for HIV/HCV-coinfected Liver Transplant Recipients in the Direct-acting Antiviral Era. Issue 7 (July 2021) - Cotter, Thomas G.; Wang, Jennifer; Lieber, Sarah R.; Odenwald, Matthew A.; Rich, Nicole E.; Marrero, Jorge A.; Singal, Amit G.; Mitchell, Mack C.; Aronsohn, Andrew; Charlton, Michael; Fung, John
Abstract : Background: The 2013 HIV Organ Policy Equity Act has increased liver transplantation (LT) in HIV + patients; however, transplant centers may remain reluctant to perform LT in HIV/hepatitis C virus (HCV)-coinfected patients due to inferior outcomes. We aimed to assess how direct-acting antivirals (DAAs) have impacted HIV + /HCV + -coinfected LT recipient outcomes. Methods: national data including 70 125 adult LT recipients between 2008 and 2019 were analyzed. Kaplan-Meier survival analysis and Cox proportional hazards model were used to analyze outcomes. Results: LT for HIV + individuals increased in the DAA era from 28 in 2014 to 64 in 2019 (23 had HIV + /HCV + coinfection). In the pre-DAA era, HIV + /HCV + -coinfected LT recipients had an increased risk of graft failure compared with HIV − /HCV − -uninfected LT recipients (hazard ratio [HR], 1.85; P < 0.001). In contrast, there was no difference in graft failure between HIV + /HCV + -coinfected versus HIV − /HCV − -uninfected LT recipients in the DAA era (HR, 1.24; P = 0.308). Among coinfected LT recipients in the DAA era, 1- and 3-y cumulative graft survivals were 88.6% and 81.7% compared with 76.3% and 58.0% in the pre-DAA era, respectively ( P = 0.006). In Cox analysis, HCV coinfection was not associated with graft failure (HR, 1.00; 95% confidence interval, 0.53-1.89) among HIV + LT recipients in the DAA era (n = 271). Black and Hispanic populations accounted for almost half of HIV + /HCV + LTs in the DAA era. Conclusions: HIV + /HCV + -coinfected LT recipient outcomes have improved significantly in the DAA era. Our results should offer reassurance to transplant centers and encourage timely transplantation referral of HIV patients with decompensated cirrhosis, including patients coinfected with HCV.